1997
DOI: 10.1097/00007890-199707150-00026
|View full text |Cite
|
Sign up to set email alerts
|

MURINE INTERLEUKIN 4 TRANSGENIC HEART ALLOGRAFT SURVIVAL PROLONGED WITH DOWN-REGULATION OF THE TH1 CYTOKINE mRNA IN GRAFTS

Abstract: A Th2 bias may contribute to allograft acceptance in part by inducing the down-regulation of Th1-cytokine mRNAs, but it may not be sufficient to induce indefinite graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…1,2,32,33 However, previous reports have shown that administration of IL-4 to rats undergoing donor-specific transfusion and treatment with cyclosporin A has been shown to prolong heart allograft survival, and survival of murine IL-4 transgenic heart allografts has been moderately prolonged compared with non-transgenic hearts. 34,35 Two of the animals treated with AdIL-4 died with signs of hepatic disfunction. Intraportal administration of AdIL-4 has been shown to result in dose-dependent lethal acute hepatitis, 19 which is partially due to an increase in anti-adenovirus immune responses, 8 but is largely due to a pro-apoptotic effect of IL-4 on hepatocytes.…”
mentioning
confidence: 99%
“…1,2,32,33 However, previous reports have shown that administration of IL-4 to rats undergoing donor-specific transfusion and treatment with cyclosporin A has been shown to prolong heart allograft survival, and survival of murine IL-4 transgenic heart allografts has been moderately prolonged compared with non-transgenic hearts. 34,35 Two of the animals treated with AdIL-4 died with signs of hepatic disfunction. Intraportal administration of AdIL-4 has been shown to result in dose-dependent lethal acute hepatitis, 19 which is partially due to an increase in anti-adenovirus immune responses, 8 but is largely due to a pro-apoptotic effect of IL-4 on hepatocytes.…”
mentioning
confidence: 99%
“…IFN-c and TNF-a, might help to predict the onset of acute and chronic GVHD after allogeneic SCT and could contribute to identify those relapsed pts after SCT who could benefit from a DLItherapy (Yamamoto et al 2004;Yang et al 2005;Ritchie et al 2005). For a long time, it was assumed that TH2 cytokines such as IL-4 and IL-10 induce T-cell anergy thereby promoting allograft tolerance, whereas TH1 cytokines such as IL-2 and IFN-c are associated with graft rejection (Sayegh et al 1995;Takeuchi et al 1997). Indeed, in our study high median levels of IL-4 and of IL-10 were detected after 'MNC'-and 'DC'-stimulation in cases without GVHD.…”
Section: Cytokine Release and Significance Of Cytokines In Clinical Tmentioning
confidence: 99%
“…IL-4 treatment of rats prolonged the survival of allogeneic neonatal hearts, 76 and similar prolongation of graft survival was seen in mice transplanted heterotopically with an allogeneic heart from a mouse transgenic for IL-4. 77 Combined treatment of IL-10 and IL-4 of non-obese diabetic (NOD) mice (a strain that develops autoimmune diabetes) prevents the recurrence of diabetes following syngeneic islet transplantation 78 whereas adenoviral gene transfer of IL-4 and IL-10 to NOD syngeneic islets fails to protect them from autoimmune destruction. 79 These results, obtained from experiments using cytokines with immunosuppressive characteristics, although promising, indicate that neither cytokine is able to prolong allogeneic organ survival as effectively or as long as treatments aimed at blockade of co-stimulation or adhesion.…”
Section: Inhibition Of Leukocyte-mediated Rejectionmentioning
confidence: 99%